Neuronal let-7b-5p acts through the Hippo-YAP pathway in neonatal encephalopathy - Vennila Ponnusamy; Richard T. H. Ip; Moumin A. E. K. Mohamed; Paul Clarke; Eva Wozniak; Charles Mein; Leslie Schwendimann; Akif Barlas; Philippa Chisholm; Ela Chakkarapani; Adina T. Michael-Titus; Pierre Gressens; et al. (Communications Biology, 2021)
Using next generation sequencing of dried blood spots and subsequent validation, Ponnusamy et al identify let-7b-5p as an elevated microRNA in neonates with moderate to severe encephalopathy. Using cell culture and murine models of perinatal brain injury they demonstrate that the effects of let-7b-5p are elicited via the Hippo-YAP pathway, which should be validated in large neonate cohorts to expand our understanding of let-7b-5p as a biomarker for neonatal encephalopathy.